Investigations of mycobacteria-specific memoryy/effector T cell responses in HIV infected children receiving antiretroviral therapy - Tena-Coki, Nontobeko Gwendoline (Institute of Infectious Disease and Molecular Medicine, 2015)
Includes abstract.